Familial dilated cardiomyopathy: A multidisciplinary entity, from basic screening to novel circulating biomarkers. (1st February 2017) - de Gonzalo-Calvo, D.; Quezada, M.; Campuzano, O.; Perez-Serra, A.; Broncano, J.; Ayala, R.; Ramos, M.; Llorente-Cortes, V.; Blasco-Turrión, S.; Morales, F.J.; Gonzalez, P.; Brugada, R.; et al.
Abstract: Idiopathic dilated cardiomyopathy has become one of the most prevalent inherited cardiomyopathies over the past decades. Genetic screening of first-degree relatives has revealed that 30–50% of the cases have a familial origin. Similar to other heart diseases, familial dilated cardiomyopathy is characterized by a high genetic heterogeneity that complicates family studies. Cli'nical screening, 12-lead electrocardiogram and transthoracic echocardiogram are recommended for patients and first-degree family members. Magnetic resonance also needs to be considered. Genetic technologies have become fundamental for the clinical management of this disease. New generation sequencing methods have made genetic testing feasible for extensive panels of genes related to the disease. Recently, new imaging modalities such as speckle-tracking, strain and strain rate or magnetic resonance, and circulating biomarkers such as non-coding RNAs, have emerged as potential strategies to help cardiologists in their clinical practice. Imaging, genetic and blood-based techniques should be considered together in the evaluation and testing of familial dilated cardiomyopathy. Here, we discuss the current procedures and novel approaches for the clinical management of familial dilated cardiomyopathy. Highlights: Familial dilated cardiomyopathies should be considered a multidisciplinary entity. Imaging, genetic and serological techniques should be considered in the evaluation of familial dilated cardiomyopathy. Implementation all these novel methods should establish genetic and cardiovascular imaging pattern in this entity, useful for clinical.